Evaluation of risk factors presence in human papilloma virus (HPV) infection and its oncogenity in rural region - Nawarra-Karowicz, Dagmara; Karowicz-Bilińska, Agata; Kowalska-Koprek, Urszula (Menopause Review/Przegląd Menopauzalny, 2005)
Objectives: The presence of human papilloma virus DNA-chain is observed in more than 90% cases of cervical cancer. The progress of neoplasia formation is depended on some known risk factors. Design. The aim of this study was to find the presence of human papilloma virus infection the presence of risk factors of infection and to evaluate the group of high or low risk of neoplasia formation viruses in rural region of Poland. Material and methods: The study was conduced in Slubice region in 2002-2003. The study group consisted of 200 women in age of 18-65. The Pap-smears were done and the samples for PCR method of HPV-infection diagnosis from the uterine cervix. The presesnce of HPV-infection risk factors was estimated. Results and conclusion: We found 4% abnormal results of cervical cytology and in 3.5% of DNA HPV presence in PCR method. 50% of infected woman had HPV of high risk of neoplasia and 37.5 % of low risk, in one case the PCR result was negative. We found the correlation between high risk HPV infection and cigarette smoking, high rate of sexual relationships and previous sexual relationships of the partner.